The art and science of using routine outcome measurement in mental health benchmarking. (February 2014) - McKay, Roderick; Coombs, Tim; Duerden, David
Objective: To report and critique the application of routine outcome measurement data when benchmarking Australian mental health services. Method: The experience of the authors as participants and facilitators of benchmarking activities is augmented by a review of the literature regarding mental health benchmarking in Australia. Results: Although the published literature is limited, in practice, routine outcome measures, in particular the Health of the National Outcomes Scales (HoNOS) family of measures, are used in a variety of benchmarking activities. Use in exploring similarities and differences in consumers between services and the outcomes of care are illustrated. This requires the rigour of science in data management and interpretation, supplemented by the art that comes from clinical experience, a desire to reflect on clinical practice and the flexibility to use incomplete data to explore clinical practice. Conclusions: Routine outcome measurement data can be used in a variety of ways to support mental health benchmarking. With the increasing sophistication of information development in mental health, the opportunity to become involved in benchmarking will continue to increase. The techniques used during benchmarking and the insights gathered may prove useful to support reflection on practice by psychiatrists and other senior mental health clinicians.